A new therapy for microcystic lymphatic malformations: the combination of intralesional laser thermolysis and percutaneous sclerotherapy - Wu, Zhiping; Zou, Yun; Fu, Ronghua; Cheng, Jun; Bai, Hanxiang; Huang, Mengyu; Yuan, Hua (Frontiers in Cell and Developmental Biology, 2024)
BackgroundOver the past few decades, percutaneous sclerotherapy has been proven to be efficacy in treating macrocystic lymphatic malformations (LMs). Unfortunately, there still remains challenging in the treatment of microcystic LMs given their size. We introduce the intralesional laser thermolysis (ILT) technique, a novel enhancement technique for the traditional percutaneous sclerotherapy in the treatment of microcystic LMs.MethodsA retrospective analysis of children with microcystic LMs treated using ILT combined with percutaneous sclerotherapy was done. All patients underwent clinically and cross-sectional imaging to assess response to treatment.ResultsBetween January 2020 and April 2022, 16 consecutive patients (female/male ratio: 7:9; average age, 32.6 months; range: 6 months to 16 years) with microcystic LMs received treatment with ILT combined with percutaneous sclerotherapy. A total of twenty-six sessions of combination therapy were performed, with a mean number of sessions per patient of 1.6 (±0.7), ranging from 1 to 3 sessions. The follow-up time ranged from 6 to 24 months, with a mean of 15.8 (±6.3) months. Almost all patients showed significant improvement after the combination therapy. No major complications were observed. Minor complications included circumscribed skin blisters, postoperative non-infectious fever, transient skin edema, pigmentation, and slight depressions of localized skin.ConclusionThe treatment of intralesional laser thermolysis combined with traditional sclerotherapy is considered as a safe, feasible and effective therapy in treating microcystic LMs.